USE OF SUBSTRATES IN THE PRODUCTION OF AÇAÍ SEEDLINGS CV. BRS PAI D'ÉGUA - da Silva, Edgley Soares; Araújo, Cássia Mônica Silva; Monteiro Neto, João Luiz Lopes; Gonçalves, Anderson Carlos de Melo; Reyes, Veronica Nathaly Arevalo; Cruz, Ana Bárbara de Souza (Seven Editora, 2026)
One of the main steps in the açaí production system is the production of quality seedlings, as the final performance of the plants in the production field depends on them. Therefore, the objective of this study was to evaluate the use of different substrates in the production of açaí seedlings cv. BRS Pai d'egua. The experiment was conducted from March to July 2022, on a private property located at Rua Áureo Cruz, 1747, Buritis neighborhood, Boa Vista, Roraima, Brazil. The design was completely randomized, with six replications. The treatments consisted of nine substrates containing different combinations of: OrganoAmazon® (AO), bovine manure (EB), carbonized rice husks (CAC) and sand, being: 1- OrganoAmazon® + bovine manure (1:1 v/v) ; 2- OrganoAmazon® + carbonized rice husk (1:1 v/v); 3- OrganoAmazon® + sand (1:1 v/v); 4- bovine manure + carbonized rice husk (1:1 v/v); 5- bovine manure + sand (1:1 v/v); 6- OrganoAmazon® + bovine manure + carbonized rice husks (1:1:1 v/v); 7- OrganoAmazon® + bovine manure + sand (1:1:1 v/v); 8- OrganoAmazon® + carbonized rice husks + sand (1:1:1 v/v); 9- bovine manure + carbonized rice husks + sand (1:1:1: v/v). It was concluded that the combinations of AO + EB + Sand and EB + CAC + Sand are excellent alternatives in the production of substrates for the production of açaí seedlings cv. BRS Pai d'egua. Substrates produced with the presence of sand are more efficient for the production of açaí seedlings cv. BRS Pai d'egua. The use of the commercial substrate OrganoAmazon® mixed with sand or CAC does not offer good growth conditions for açaí seedlings cv. BRS Pai d'egua.